Endothelin-1 concentrations are correlated with the severity of knee osteoarthritis. Issue 4 (25th February 2016) - Zhao, Zhe; Li, Enqi; Cao, Qing; Sun, Jie; Ma, Baotong
Abstract : Endothelin-1, a potent vasoconstrictor regulator, contributes to articular cartilage destruction. Therefore, we aim to assess the correlation of endothelin-1 concentrations with the development and severity of knee osteoarthritis (OA). This study included a population of 209 patients with knee OA. Kellgren-Lawrence (KL) grading was utilized to score the severity of OA. The case group had higher serum endothelin-1 concentrations than controls. Patients with knee OA with a relatively higher grade showed significantly elevated serum and synovial fluid (SF) endothelin-1 concentrations compared with those with lower KL grades. A significant correlation was found between serum and SF endothelin-1 concentrations and KL grades. Serum and SF endothelin-1 concentrations are correlated with the development and progression of knee OA.